Klärung und Neubeschreibung der Sandbiene Andrena asiatica Friese, 1921 (Hymenoptera: Apidae, Andreninae). - Schuberth, Johannes; Grünwaldt, Robert Wilhelm; Schönitzer, Klaus (Contributions to Entomology = Beiträge zur Entomologie, 2001)
Andrena asiatica Friese, 1921 is redescribed and a lectotype is designated. The brighter haired subspecies, A. asiatica oxyura Warncke, 1975 is a synonym of the nominate form (syn. n.). A. asiatica does not belong to the subgenus Nobandrena but is probably related to A. formosa Morawitz, 1878 and A. combusta Morawitz, 1876. Nomenclatural Acts asiatica Friese, 1921 (Andrena), Lectotype